Method and system for producing natural gas by methanation of synthesis gas
By using adiabatic methanation reaction of paraffin cracking catalyst and high-temperature methanation catalyst in low-temperature methanation production, paraffin in the slurry bed outlet process gas is directly removed, solving the problems of catalyst deactivation and equipment, and achieving efficient methane production.
Patent Information
- Application Number
- CN202311145598.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2043-09-06
AI Technical Summary
In the existing methods for producing natural gas in low-temperature methanation, the export process gas of the slurry bed contains paraffin, which leads to the deactivation of the catalyst and requires multiple wax removal equipment, which increases the number of equipment and heat loss.
After the methanation reaction is carried out in the slurry bed reactor, the adiabatic methanation reaction is performed using Catalyst II, which contains the paraffin cracking catalyst and the high-temperature methanation catalyst, to directly remove the paraffin from the export process gas to avoid condensation and dehydration steps.
The one-step removal of paraffin from gas from the slurry bed export process is achieved, which avoids catalyst deactivation and multi-equipment use, reduces heat loss and equipment investment, and increases methane production.
Smart Images

Figure CN119570539A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of comprehensive application of coal gasification, and in particular to a method and system for producing natural gas by methanation of synthesis gas. Background Art
[0002] Synthesis gas is composed of CH4, H2, CO, and CO2, and is an ideal raw material gas for the production of SNG / LNG. Converting synthesis gas into natural gas can produce good economic and social benefits. Developing suitable synthesis gas to methane technology based on the composition of synthesis gas is an effective way to realize the utilization of synthesis gas, which is of great significance.
[0003] At present, low-temperature methanation technology has gradually become a new direction for methane production. Low-temperature methanation is widely used in the production of methane due to its high chemical balance, large processing capacity, less equipment and no need for circulation. The slurry bed is a more advanced reaction equipment in the low-temperature process. The temperature in its reaction area is highly uniform, and it is extremely difficult to have a temperature runaway or local temperature is too high. The heat transfer is fast and the methanation efficiency is high. The slurry bed process performs well in methanation production. However, the slurry bed methanation process is limited by the process. The outlet process gas of the slurry bed contains paraffin vapor and paraffin entrained by liquid foam. It needs to be cooled, condensed and separated, and then heat exchanged and heated before entering the subsequent refining process. The cooling, condensing and heating process requires several equipment such as condensers, separation tanks, cold water circulation pumps, heat exchangers, heaters, etc., accompanied by heat loss and power consumption. The separated paraffin and water mixture increases the sewage discharge pressure as wastewater. If the process gas at the outlet of the slurry bed directly enters the subsequent refining stage without heat exchange, paraffin will be enriched on the surface of the subsequent refined catalyst, covering the surface of the catalyst to form a phenomenon similar to catalyst waxing, causing the catalyst to gradually physically deactivate. Summary of the invention
[0004] The purpose of the present invention is to overcome the problem that in the existing method for producing natural gas by low-temperature methanation, the outlet process gas of the slurry bed contains paraffin, which easily deactivates the catalyst and requires multiple wax removal equipment.
[0005] In order to achieve the above object, the present invention provides a method for producing natural gas by methanation of synthesis gas in a first aspect, the method comprising:
[0006] (1) In a slurry bed reactor, the synthesis gas is contacted with a catalyst I for a methanation reaction to obtain an export process gas containing paraffin; the catalyst I is a low-temperature methanation catalyst;
[0007] (2) contacting the outlet process gas with catalyst II to carry out an adiabatic methanation reaction;
[0008] Wherein, the catalyst II comprises a paraffin cracking catalyst and a high-temperature methanation catalyst; the paraffin cracking catalyst comprises a carrier and an active component and an auxiliary agent loaded on the carrier, wherein the active component is manganese dioxide, the auxiliary agent is La2O3, the carrier is a magnesium-aluminum composite oxide, the magnesium-aluminum composite oxide comprises MgAl2O4, and based on the total amount of the magnesium-aluminum composite oxide, the content of MgAl2O4 is 93-100wt%; based on the total amount of the paraffin cracking catalyst, the content of the active component is 5-15wt%, the content of the auxiliary agent is 0.1-2wt%, and the content of the carrier is 83-94.9wt%; or,
[0009] The catalyst II is a bifunctional catalyst, which includes a carrier and an active component I, an active component II and an auxiliary agent loaded on the carrier, wherein the active component I is nickel and / or nickel oxide, the active component II is manganese dioxide, the auxiliary agent is La2O3, the carrier is a magnesium-aluminum composite oxide, and the magnesium-aluminum composite oxide includes MgAl2O4, and the content of MgAl2O4 is 93-100wt% based on the total amount of the magnesium-aluminum composite oxide; based on the total amount of the bifunctional catalyst, the content of the active component I in terms of nickel is 10-20wt%, the content of the active component II is 5-15wt%, the content of the auxiliary agent is 0.1-2wt%, and the content of the carrier is 74-85wt%.
[0010] A second aspect of the present invention provides a system for producing natural gas by methanation of synthesis gas, the system comprising a methanation unit and a refining unit connected in series, wherein the methanation unit comprises at least one slurry bed reactor, the refining unit comprises at least one adiabatic fixed bed reactor, and the outlet of the slurry bed reactor is connected to the inlet of the adiabatic fixed bed reactor.
[0011] Through the above technical scheme, the method provided by the present invention subjects the synthesis gas to a slurry bed methanation reaction, and the obtained export process gas containing paraffin can directly undergo an adiabatic methanation reaction (high-temperature refining) without undergoing condensation and dehydration steps. The high temperature and heat generated by the adiabatic methanation reaction can meet the reaction process conditions required for the steam cracking of trace paraffin in the export process gas of the slurry bed. By utilizing this condition and under the action of a catalyst having a high-temperature methanation catalytic effect and a high-temperature dewaxing catalytic effect, the effect of removing the trace paraffin contained in the export process gas of the slurry bed can be achieved without condensation separation.
[0012] The method provided by the present invention can remove the trace paraffin contained in the process gas at the outlet of the slurry bed in one step, and crack it to convert it into small molecular hydrocarbons, thereby avoiding the catalyst being covered by paraffin and deactivated in the subsequent refining process, which is beneficial to reducing the number of intermediate links and equipment, shortening the process of producing natural gas by methanation of synthesis gas, reducing the heat loss caused by heating and cooling, and reducing the equipment investment and operation cost. In addition, since the paraffin is cracked into methane, it is also beneficial to increase the methane output. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1 It is a schematic diagram of a system for producing natural gas by methanation of synthesis gas according to one embodiment of the present invention;
[0014] Figure 2 is the XRD diagram of the carriers prepared in Preparation Example A1 and Preparation Example B1 of the present invention;
[0015] Figure 3 is the XRD pattern of the reduction product obtained in step (S1) of Preparation Example C1 of the present invention;
[0016] Figure 4 It is the XRD diagram of the dispersant used in Preparation Example C1 of the present invention.
[0017] Description of Reference Numerals
[0018] 1. Slurry bed reactor 2. Valve
[0019] 3. One-way check valve 4. Adiabatic fixed bed reactor DETAILED DESCRIPTION
[0020] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0021] In the present invention, unless otherwise stated, the content of each component in the paraffin cracking catalyst and the bifunctional catalyst is calculated by the feed amount.
[0022] In the present invention, unless otherwise stated, the pressure is a gauge pressure.
[0023] In the present invention, unless otherwise specified, the room temperature refers to 25±2°C.
[0024] As mentioned above, the first aspect of the present invention provides a method for producing natural gas by methanation of synthesis gas, the method comprising:
[0025] (1) In a slurry bed reactor, the synthesis gas is contacted with a catalyst I for a methanation reaction to obtain an export process gas containing paraffin; the catalyst I is a low-temperature methanation catalyst;
[0026] (2) contacting the outlet process gas with catalyst II to carry out an adiabatic methanation reaction;
[0027] Wherein, the catalyst II comprises a paraffin cracking catalyst and a high-temperature methanation catalyst; the paraffin cracking catalyst comprises a carrier and an active component and an auxiliary agent loaded on the carrier, wherein the active component is manganese dioxide, the auxiliary agent is La2O3, the carrier is a magnesium-aluminum composite oxide, the magnesium-aluminum composite oxide comprises MgAl2O4, and based on the total amount of the magnesium-aluminum composite oxide, the content of MgAl2O4 is 93-100wt%; based on the total amount of the paraffin cracking catalyst, the content of the active component is 5-15wt%, the content of the auxiliary agent is 0.1-2wt%, and the content of the carrier is 83-94.9wt%; or,
[0028] The catalyst II is a bifunctional catalyst, which includes a carrier and an active component I, an active component II and an auxiliary agent loaded on the carrier, wherein the active component I is nickel and / or nickel oxide, the active component II is manganese dioxide, the auxiliary agent is La2O3, the carrier is a magnesium-aluminum composite oxide, and the magnesium-aluminum composite oxide includes MgAl2O4, and the content of MgAl2O4 is 93-100wt% based on the total amount of the magnesium-aluminum composite oxide; based on the total amount of the bifunctional catalyst, the content of the active component I in terms of nickel is 10-20wt%, the content of the active component II is 5-15wt%, the content of the auxiliary agent is 0.1-2wt%, and the content of the carrier is 74-85wt%.
[0029] According to some embodiments of the present invention, in step (2), the catalyst II is a catalyst having a high-temperature methanation catalytic effect and a high-temperature dewaxing catalytic effect. The catalyst II may be a mixture of two or more catalysts having a high-temperature methanation catalytic effect and a high-temperature dewaxing catalytic effect, respectively, or may be a single catalyst having both a high-temperature methanation catalytic effect and a high-temperature dewaxing catalytic effect.
[0030] According to some embodiments of the present invention, in step (2), the catalyst II comprises a paraffin cracking catalyst and a high-temperature methanation catalyst; the paraffin cracking catalyst comprises a carrier and an active component and an auxiliary agent loaded on the carrier, wherein the active component is manganese dioxide, the auxiliary agent is La2O3, the carrier is a magnesium-aluminum composite oxide, the magnesium-aluminum composite oxide comprises MgAl2O4, and the content of MgAl2O4 is 93-100wt% based on the total amount of the magnesium-aluminum composite oxide;
[0031] Based on the total amount of the paraffin cracking catalyst, the content of the active component is 5-15wt%, the content of the auxiliary agent is 0.1-2wt%, and the content of the carrier is 83-94.9wt%.
[0032] According to some embodiments of the present invention, preferably, based on the total amount of the magnesium-aluminum composite oxide, the content of MgAl2O4 is 96-100 wt%.
[0033] According to some embodiments of the present invention, preferably, the magnesium-aluminum composite oxide further comprises MgO and / or Al2O3. The MgO is the residual magnesium oxide that has not formed magnesium-aluminum spinel (MgAl2O4); the Al2O3 is the residual aluminum oxide that has not formed magnesium-aluminum spinel (MgAl2O4).
[0034] Preferably, based on the total amount of the magnesium-aluminum composite oxide, the content of MgO is 0-5wt%, preferably 0-3wt%; the content of Al2O3 is 0-2wt%, preferably 0-1wt%.
[0035] By adopting the above preferred embodiment, the residual aluminum oxide content in the magnesium aluminum composite oxide is small, which is beneficial to reducing the acidic sites therein. If there is too much aluminum oxide, during the paraffin cracking process, the relatively stable α carbon is converted into the relatively active β carbon at the acidic site, which easily causes the growth of carbon nanotubes generated on the catalyst surface, thereby causing the catalyst to be carbonized and deactivated. The low residual aluminum oxide content in the magnesium aluminum composite oxide can avoid the above-mentioned carbonization and deactivation problem, which is beneficial to improving the activity and service life of the catalyst.
[0036] According to some embodiments of the present invention, preferably, the grain size of MgAl2O4 is less than 20nm, preferably 4-15nm, and more preferably 5-10nm. The above preferred embodiment is helpful to improve the dispersion of the active component on the carrier surface and to fix the active component together with the auxiliary agent, thereby preventing the carbon nanotubes from lifting the active component from the carrier and causing it to be lost.
[0037] According to some embodiments of the present invention, preferably, the pore volume of MgAl2O4 is >0.15 mL / g, preferably 0.25-0.35 mL / g, and more preferably 0.27-0.33 mL / g.
[0038] According to some embodiments of the present invention, preferably, the average pore size of MgAl2O4 is 10-50 nm, preferably 10-30 nm, and more preferably 13-20 nm.
[0039] By adopting the above preferred embodiment, the grain size, pore volume and average pore size of MgAl2O4 meet the above conditions, which is beneficial to control the impregnation amount of active components during the catalyst preparation process, as well as the diffusion of paraffin molecules in the catalyst pores and the escape of paraffin cracking products.
[0040] According to some embodiments of the present invention, preferably, in the magnesium-aluminum composite oxide, the molar ratio of Mg to Al is 1:2-2.04.
[0041] According to some embodiments of the present invention, the paraffin cracking catalyst does not need to be activated, but is directly active and can be used directly.
[0042] According to some embodiments of the present invention, preferably, the paraffin cracking catalyst is prepared by a method comprising the following steps:
[0043] (A1) subjecting a mixture containing magnesium oxide, pseudo-boehmite and a pore-enlarging agent to a first calcination to obtain a carrier; wherein the temperature of the first calcination is 800-1000° C.;
[0044] (A2) loading the active component precursor and the auxiliary agent precursor onto the carrier, and then subjecting the obtained product to a second calcination; wherein the temperature of the second calcination is lower than the temperature of the first calcination.
[0045] According to some embodiments of the present invention, preferably, in step (A1), the temperature of the first calcination is 850-950° C. The above preferred embodiment is more conducive to increasing the content of MgAl2O4 in the magnesium-aluminum composite oxide and reducing the content of Al2O3, thereby reducing the carbon deposits generated during the paraffin cracking process and improving the activity and service life of the catalyst.
[0046] According to some embodiments of the present invention, preferably, in step (A1), the first calcination time is 2-10 h, preferably 4-8 h.
[0047] According to some embodiments of the present invention, preferably, in step (A1), the magnesium oxide is light magnesium oxide, and the average particle size of the light magnesium oxide is 0.06-0.09 mm.
[0048] According to some embodiments of the present invention, preferably, in step (A1), the average particle size of the pseudo-boehmite is 0.06-0.09 mm.
[0049] Using the raw materials of the above preferred embodiment is more conducive to obtaining a carrier that meets the above requirements.
[0050] According to some embodiments of the present invention, preferably, in step (A1), the pore expanding agent is selected from at least one of oxalic acid, nitric acid, acetic acid and sulfuric acid, preferably nitric acid.
[0051] Preferably, the usage ratio of the pore expanding agent to the magnesium oxide is 1 mL: 40-60 g.
[0052] According to some embodiments of the present invention, in order to facilitate molding, preferably, in step (A1), the mixture further contains a binder.
[0053] Preferably, the binder is selected from at least one of sesbania powder, stearate, cellulose and its derivatives, preferably sodium carboxymethyl cellulose.
[0054] Preferably, the mass ratio of the binder to the magnesium oxide is 1:20-25.
[0055] According to some embodiments of the present invention, in order to ensure that the components in the mixture are fully dispersed and have appropriate strength for subsequent molding, preferably, in step (A1), the mixture further contains a solvent.
[0056] Preferably, the solvent is deionized water.
[0057] Preferably, the volume ratio of the solvent to the pore-enlarging agent is 80-150:1.
[0058] According to some embodiments of the present invention, preferably, before the first calcination, step (A1) further comprises the steps of mixing, grinding, sieving, drying and molding in sequence. The steps of mixing, grinding, sieving, drying and molding are conventional means for preparing catalysts and can be performed with reference to the prior art.
[0059] According to some embodiments of the present invention, preferably, in step (A2), the active component precursor is selected from at least one of manganese nitrate, manganese sulfate and manganese chloride, preferably manganese nitrate. Preferably, the active component precursor is provided in the form of an aqueous solution. Exemplarily, the manganese nitrate can be provided in the form of a 50wt% manganese nitrate aqueous solution.
[0060] According to some embodiments of the present invention, preferably, in step (A2), the auxiliary agent precursor is selected from at least one of lanthanum nitrate, lanthanum chloride and lanthanum sulfate, preferably lanthanum nitrate. Preferably, the auxiliary agent precursor is provided in the form of an aqueous solution. Exemplarily, the lanthanum nitrate can be provided in the form of a 4wt% lanthanum nitrate aqueous solution.
[0061] According to some embodiments of the present invention, preferably, in step (A2), the conditions of the second calcination include: a temperature of 350-500° C., preferably 400-450° C.; and a time of 4-10 h, preferably 4-8 h.
[0062] According to some embodiments of the present invention, preferably, in step (A2), the loading method is an impregnation method;
[0063] Preferably, the immersion conditions include: temperature of 60-80°C; time of 0.5-2h;
[0064] Preferably, the active component precursor is first loaded on the carrier to obtain an intermediate, and then the auxiliary agent precursor is loaded on the intermediate. After each component is impregnated, it needs to be dried and calcined to fix the component. The drying can be performed with reference to the prior art.
[0065] According to a preferred embodiment of the present invention, in step (A2), the loading step includes:
[0066] (A2-a) contacting the support with the active component precursor for a first impregnation, filtering the obtained product, and then sequentially drying and second calcining the obtained solid I to obtain an intermediate;
[0067] (A2-b) contacting the intermediate with the auxiliary agent precursor for a second impregnation, filtering the obtained product, and then drying and second calcining the obtained solid in sequence II;
[0068] The conditions of the first impregnation and the second impregnation independently include: temperature of 60-80°C; time of 0.5-2h; the conditions of the second calcination I and the second calcination II independently include: temperature of 350-500°C, preferably 400-450°C; time of 4-10h, preferably 4-8h.
[0069] According to some embodiments of the present invention, in step (2), the catalyst II is a bifunctional catalyst. The bifunctional catalyst comprises a carrier and an active component I, an active component II and an auxiliary agent supported on the carrier, wherein the active component I is nickel and / or nickel oxide, the active component II is manganese dioxide, the auxiliary agent is La2O3, the carrier is a magnesium-aluminum composite oxide, the magnesium-aluminum composite oxide comprises MgAl2O4, and the content of MgAl2O4 is 93-100wt% based on the total amount of the magnesium-aluminum composite oxide;
[0070] Based on the total amount of the bifunctional catalyst, the content of the active component I in terms of nickel is 10-20wt%, the content of the active component II is 5-15wt%, the content of the auxiliary agent is 0.1-2wt%, and the content of the carrier is 74-85wt%.
[0071] According to some embodiments of the present invention, preferably, based on the total amount of the magnesium-aluminum composite oxide, the content of MgAl2O4 is 96-100 wt%.
[0072] According to some embodiments of the present invention, the magnesium-aluminum composite oxide preferably further comprises MgO and / or Al2O3, wherein the MgO is residual magnesium oxide that has not formed magnesium-aluminum spinel (MgAl2O4); and the Al2O3 is residual aluminum oxide that has not formed magnesium-aluminum spinel (MgAl2O4).
[0073] Preferably, based on the total amount of the magnesium-aluminum composite oxide, the content of MgO is 0-5wt%, preferably 0-3wt%; the content of Al2O3 is 0-2wt%, preferably 0-1wt%.
[0074] By adopting the above preferred embodiment, the residual aluminum oxide content in the magnesium aluminum composite oxide is small, which is beneficial to reducing the acidic sites therein. If there is too much aluminum oxide, during the paraffin cracking process, the relatively stable α carbon is converted into the relatively active β carbon at the acidic site, which easily causes the growth of carbon nanotubes generated on the catalyst surface, thereby causing the catalyst to be carbonized and deactivated. The low residual aluminum oxide content in the magnesium aluminum composite oxide can avoid the above-mentioned carbonization and deactivation problem, which is beneficial to improving the activity and service life of the catalyst.
[0075] According to some embodiments of the present invention, preferably, the grain size of MgAl2O4 is less than 20nm, preferably 4-15nm, and more preferably 5-10nm. The above preferred embodiment is helpful to improve the dispersion of the active component on the carrier surface and to fix the active component together with the auxiliary agent, thereby preventing the carbon nanotubes from lifting the active component from the carrier and causing it to be lost.
[0076] According to some embodiments of the present invention, preferably, the pore volume of MgAl2O4 is >0.15 mL / g, preferably 0.25-0.35 mL / g, and more preferably 0.27-0.33 mL / g.
[0077] According to some embodiments of the present invention, preferably, the average pore size of MgAl2O4 is 10-50 nm, preferably 10-30 nm, and more preferably 13-20 nm.
[0078] By adopting the above preferred embodiment, the grain size, pore volume and average pore size of MgAl2O4 meet the above conditions, which is beneficial to control the impregnation amount of active components during the catalyst preparation process, as well as the diffusion of paraffin molecules in the catalyst pores and the escape of paraffin cracking products.
[0079] According to some embodiments of the present invention, preferably, in the magnesium-aluminum composite oxide, the molar ratio of Mg to Al is 1:2-2.04.
[0080] According to some embodiments of the present invention, in the bifunctional catalyst, the active component I is present in the form of nickel and / or nickel oxide. The nickel oxide can be reduced to active nickel by contacting with a reducing gas for activation and reduction.
[0081] According to some embodiments of the present invention, preferably, the bifunctional catalyst is prepared by a method comprising the following steps:
[0082] (B1) subjecting a mixture containing magnesium oxide, pseudo-boehmite and a pore-enlarging agent to a first calcination to obtain a carrier; wherein the temperature of the first calcination is 800-1000° C.;
[0083] (B2) loading the active component precursor I, the active component precursor II and the auxiliary agent precursor on the carrier, and then performing a second calcination on the obtained product; wherein the temperature of the second calcination is lower than the temperature of the first calcination.
[0084] According to some embodiments of the present invention, preferably, in step (B1), the temperature of the first calcination is 850-950° C. The above preferred embodiment is more conducive to increasing the content of MgAl2O4 in the magnesium-aluminum composite oxide and reducing the content of Al2O3, thereby reducing the carbon deposits generated during the paraffin cracking process and improving the activity and service life of the catalyst.
[0085] According to some embodiments of the present invention, preferably, in step (B1), the first calcination time is 2-10 h, preferably 4-8 h.
[0086] According to some embodiments of the present invention, preferably, in step (B1), the magnesium oxide is light magnesium oxide, and the average particle size of the light magnesium oxide is 0.06-0.09 mm.
[0087] According to some embodiments of the present invention, preferably, in step (B1), the average particle size of the pseudo-boehmite is 0.06-0.09 mm.
[0088] Using the raw materials of the above preferred embodiment is more conducive to obtaining a carrier that meets the above requirements.
[0089] According to some embodiments of the present invention, preferably, in step (B1), the pore expanding agent is selected from at least one of oxalic acid, nitric acid, acetic acid and sulfuric acid, preferably nitric acid.
[0090] Preferably, the usage ratio of the pore expanding agent to the magnesium oxide is 1 mL: 40-60 g.
[0091] According to some embodiments of the present invention, in order to facilitate molding, preferably, in step (B1), the mixture further contains a binder.
[0092] Preferably, the binder is selected from at least one of sesbania powder, stearate, cellulose and its derivatives, preferably sodium carboxymethyl cellulose.
[0093] Preferably, the mass ratio of the binder to the magnesium oxide is 1:20-25.
[0094] According to some embodiments of the present invention, in order to ensure that the components in the mixture are fully dispersed and have appropriate strength for subsequent molding, preferably, in step (B1), the mixture further contains a solvent.
[0095] Preferably, the solvent is deionized water.
[0096] Preferably, the volume ratio of the solvent to the pore-enlarging agent is 80-150:1.
[0097] According to some embodiments of the present invention, preferably, before the first calcination, step (B1) further comprises the steps of mixing, grinding, sieving, drying and molding in sequence. The steps of mixing, grinding, sieving, drying and molding are conventional means for preparing catalysts and can be performed with reference to the prior art.
[0098] According to some embodiments of the present invention, preferably, in step (B2), the active component precursor I is selected from at least one of nickel nitrate, nickel chloride and nickel sulfate, preferably nickel nitrate. Preferably, the active component precursor I is provided in the form of an aqueous solution. Exemplarily, the nickel nitrate can be provided in the form of a 60wt% nickel nitrate aqueous solution.
[0099] According to some embodiments of the present invention, preferably, in step (B2), the active component precursor II is selected from at least one of manganese nitrate, manganese sulfate and manganese chloride, preferably manganese nitrate. Preferably, the active component precursor II is provided in the form of an aqueous solution. Exemplarily, the manganese nitrate can be provided in the form of a 50wt% manganese nitrate aqueous solution.
[0100] According to some embodiments of the present invention, preferably, in step (B2), the auxiliary agent precursor is selected from at least one of lanthanum nitrate, lanthanum chloride and lanthanum sulfate, preferably lanthanum nitrate. Preferably, the auxiliary agent precursor is provided in the form of an aqueous solution. Exemplarily, the lanthanum nitrate can be provided in the form of a 4wt% lanthanum nitrate aqueous solution.
[0101] According to some embodiments of the present invention, preferably, in step (B2), the conditions of the second calcination include: a temperature of 350-500° C., preferably 400-450° C.; and a time of 4-10 h, preferably 4-8 h.
[0102] According to some embodiments of the present invention, preferably, in step (B2), the loading method is an impregnation method;
[0103] Preferably, the immersion conditions include: temperature of 60-80°C; time of 0.5-2h;
[0104] Preferably, the active component precursor I is first loaded on the carrier to obtain intermediate I, then the active component precursor II is loaded on the intermediate I to obtain intermediate II, and finally the auxiliary agent precursor is loaded on the intermediate II. After each component is impregnated, it is necessary to dry and roast to fix the component. The drying can be carried out with reference to the prior art.
[0105] According to a preferred embodiment of the present invention, in step (B2), the loading step includes:
[0106] (B2-a) contacting the support with the active component precursor I for a first impregnation, filtering the obtained product, and then sequentially drying and second calcining the obtained solid I to obtain an intermediate I;
[0107] (B2-b) contacting the intermediate I with the active component precursor II for a second impregnation, filtering the obtained product, and then drying and second calcining the obtained solid in sequence II to obtain the intermediate II;
[0108] (B2-c) contacting the intermediate II with the auxiliary agent precursor for a third impregnation, filtering the obtained product, and then drying and second calcining the obtained solid in sequence III;
[0109] The conditions of the first impregnation, the second impregnation and the third impregnation are independently as follows: the temperature is 60-80°C; the time is 0.5-2h;
[0110] The conditions of the second calcination I, the second calcination II and the second calcination III independently include: a temperature of 350-500° C., preferably 400-450° C.; and a time of 4-10 h, preferably 4-8 h.
[0111] According to some embodiments of the present invention, preferably, the method for preparing the bifunctional catalyst further comprises: contacting the product obtained by the second calcination in step (B2) with a reducing gas for reduction. The above operation can reduce the nickel oxide to active nickel.
[0112] Preferably, the reducing gas is hydrogen or a mixture of hydrogen and nitrogen. For example, the mixture is a mixture with a hydrogen content of 20% by volume and a nitrogen content of 80% by volume.
[0113] Preferably, the reduction conditions include: temperature of 400-500° C.; time of 2-6 h.
[0114] According to some embodiments of the present invention, in step (1), the low-temperature methanation catalyst can be a low-temperature methanation catalyst with methanation catalytic effect conventionally used in the art (the operating temperature is usually 260-350°C), for example, it can be a slurry bed methanation catalyst, there is no particular limitation on this, and it can achieve the purpose of the present invention to a certain extent.
[0115] According to a preferred embodiment of the present invention, the low-temperature methanation catalyst comprises catalyst particles and a protective agent wrapping the catalyst particles, the catalyst particles contain amorphous nickel and a dispersant; the dispersant is a mixture of zirconium oxide and magnesium oxide, in which the mass ratio of zirconium oxide to magnesium oxide is (1-10):1, preferably (3-6):1; the crystal form of the zirconium oxide is tetragonal. The low-temperature methanation catalyst using the above preferred embodiment has a stronger hydrogenation capacity.
[0116] According to some embodiments of the present invention, preferably, in the XRD spectrum of the low-temperature methanation catalyst, there is a diffraction peak with a peak width greater than 5° at 2θ=45±0.2°. The wide diffraction peak is a diffuse peak type formed by amorphous diffuse reflection, which is the main characteristic diffraction peak of amorphous nickel. The short and wide diffuse peak indicates that the nickel in the low-temperature methanation catalyst exists in an amorphous structure.
[0117] According to some embodiments of the present invention, there is no particular restriction on the content of the protective agent in the low-temperature methanation catalyst, as long as it can wrap the catalyst particles to isolate oxygen. Preferably, in the low-temperature methanation catalyst, the content of the protective agent is 2-4 mL relative to 1 g of the catalyst particles. By adopting the above preferred embodiment, the catalyst particles can be wrapped and isolated from oxygen when the content of the protective agent is low.
[0118] When the low-temperature methanation catalyst is used, an inert heat-conducting medium can be introduced into the slurry bed reactor to adjust the volume of the slurry (inert heat-conducting medium + protective agent); preferably, the inert heat-conducting medium is the same as the protective agent. The amount of the inert heat-conducting medium introduced can be adjusted according to actual conditions, and there is no particular restriction on this.
[0119] Preferably, the amount of the inert heat-conducting medium introduced is such that the loading amount of the low-temperature methanation catalyst and the volumetric usage of the inert heat-conducting medium satisfy: relative to 1g of catalyst particles, the total amount of the protective agent and the inert heat-conducting medium in the low-temperature methanation catalyst is 20-100mL, preferably 20-50mL. The content of the protective agent in the low-temperature methanation catalyst can also be adjusted to control the loading amount of the low-temperature methanation catalyst, so that the content of the catalyst particles and the protective agent meets the above requirements.
[0120] According to some embodiments of the present invention, preferably, based on the total weight of the catalyst particles, the content of amorphous nickel in the catalyst particles is 65-75% by weight, and the content of the dispersant is 25-35% by weight.
[0121] According to some embodiments of the present invention, preferably, the particle size of the dispersant is 100-400 mesh, preferably 120-180 mesh.
[0122] According to some embodiments of the present invention, preferably, the protective agent is liquid paraffin.
[0123] According to some embodiments of the present invention, preferably, the low temperature methanation catalyst is prepared by a method comprising the following steps:
[0124] (C1) contacting the nickel precursor with a reducing agent in the presence of water to perform a reduction reaction to obtain a reduction product;
[0125] (C2) mixing the reduction product with a dispersant in the presence of a protective agent, and allowing the obtained mixture to stand for stratification to form a stratified liquid; wherein the stratified liquid comprises an upper layer liquid and a lower layer liquid, the upper layer liquid contains the protective agent, the lower layer liquid contains water and catalyst particles, and the catalyst particles contain amorphous nickel and a dispersant;
[0126] (C3) adjusting the pH value of the lower layer liquid in the layered liquid to 7-9 using water, and then removing the water in the lower layer liquid, so that the protective agent wraps the catalyst particles.
[0127] According to some embodiments of the present invention, in step (C1), in the presence of water, the nickel precursor is contacted with a reducing agent to perform a reduction reaction to obtain a reduction product. This step can reduce the nickel element in the nickel precursor to metallic nickel, and finally obtain a reduction product containing amorphous elemental nickel.
[0128] According to some embodiments of the present invention, in step (C1), the nickel precursor is a compound containing nickel element. There is no particular limitation on the type of the nickel precursor, and it can be a conventional choice in the art, for example, it can be a conventional water-soluble nickel salt in the art. Preferably, the nickel precursor is selected from at least one of nickel nitrate, nickel chloride and nickel acetate, preferably nickel nitrate.
[0129] According to some embodiments of the present invention, in step (C1), there is no particular limitation on the type of the reducing agent, and it can be any conventional choice in the art, as long as it can reduce the nickel element in the nickel precursor to amorphous nickel. Preferably, the reducing agent is a borohydride, preferably sodium borohydride and / or potassium borohydride.
[0130] According to some embodiments of the present invention, preferably, the molar ratio of the reducing agent to the nickel precursor calculated as nickel element is (1-2.5):1, preferably (1.5-2):1. The above preferred embodiments can further promote the generation of amorphous nickel particles by chemical reduction.
[0131] According to some embodiments of the present invention, preferably, in step (C1), the nickel precursor is provided in the form of a nickel precursor aqueous solution, and more preferably, the concentration of nickel element in the nickel precursor aqueous solution is 0.5-2 mol / L.
[0132] According to some embodiments of the present invention, preferably, in step (C1), the reducing agent is provided in the form of an aqueous reducing agent solution, and more preferably, the concentration of the reducing agent in the aqueous reducing agent solution is 1-3 mol / L.
[0133] According to some embodiments of the present invention, in order to remove oxygen from the solution, further promote the generation of reduction products, and improve the dispersion of reduction products, preferably, in step (C1), the contacting includes: under oscillation, dropping the nickel precursor aqueous solution into the reducing agent aqueous solution. Wherein, the conditions and methods of the oscillation and the dropping can be conventionally selected in the art, and there is no particular limitation on this, as long as the nickel element in the nickel precursor can be reduced to amorphous nickel. For example, the frequency of the oscillation can be 20-50Hz; the speed of the dropping can be 2-6 drops / second.
[0134] According to some embodiments of the present invention, preferably, in step (C1), the conditions of the reduction reaction include: temperature of 15-25° C., and time of 1-3 h.
[0135] According to some embodiments of the present invention, in order to better precipitate and separate the reduction product, preferably, in step (C1), after the dropwise addition is completed, a magnetic substance or device can be used to assist the precipitation of the reduction product during the reduction reaction.
[0136] According to some embodiments of the present invention, in step (C2), the reduction product is mixed with a dispersant in the presence of a protective agent, and the obtained mixture is allowed to stand for stratification to form a stratified liquid. This step allows the amorphous nickel in the reduction product to be fully contacted with the dispersant, which is conducive to the amorphous nickel being fully mixed with the dispersant during the sedimentation process.
[0137] According to some embodiments of the present invention, in step (C2), the protective agent is a hydrophobic inert liquid that is immiscible with water, so the mixture will form a stratified liquid during the subsequent standing stratification process, and the stratified liquid includes an upper layer liquid and a lower layer liquid; the density of the protective agent is smaller than that of water, and the catalyst particles will sink due to gravity, so in the formed stratified liquid, the upper layer liquid contains the protective agent, the lower layer liquid contains water and catalyst particles, and the catalyst particles contain amorphous nickel and a dispersant.
[0138] According to some embodiments of the present invention, the protective agent is liquid paraffin. After the static stratification, the protective agent can form a protective layer (upper layer liquid) above the lower layer liquid to isolate the oxidizing substances.
[0139] According to some embodiments of the present invention, preferably, the protective agent is used in an amount such that the thickness of the upper layer liquid is 2-3 cm.
[0140] According to some embodiments of the present invention, in step (C2), the dispersant can be used as a carrier for dispersing the slurry bed catalyst to disperse the amorphous nickel so that it does not float above the slurry (protective agent). The crystal form of the zirconium oxide is a tetragonal crystal form, which has a better auxiliary hydrogenation effect when it contacts the nickel at the midpoint of the slurry bed. The crystal form of the zirconium oxide can be determined by the XRD spectrum of the catalyst.
[0141] According to some embodiments of the present invention, preferably, the dispersant is a mixture of zirconium oxide and magnesium oxide, in which the mass ratio of zirconium oxide to magnesium oxide is (1-10):1, preferably (3-6):1, wherein the crystal form of the zirconium oxide is tetragonal. By adopting the above preferred embodiment, the pH value of the contact point between the amorphous nickel and the dispersant in the slurry bed can be adjusted, and the Zr-Ni can form a semi-load relationship with each other, which can further promote the methanation catalytic effect.
[0142] According to a preferred embodiment of the present invention, the mixture of zirconium oxide and magnesium oxide is prepared by a method comprising the following steps:
[0143] The zirconium oxide powder and magnesium oxide powder are sieved separately, and particles with a particle size of 100-400 mesh, preferably 120-180 mesh, are selected for blending (the mass ratio of zirconium oxide powder and magnesium oxide powder can be selected as described above), and then the obtained mixture is calcined at high temperature to transform the zirconium oxide from a monoclinic form to a tetragonal form, and the calcined product is cooled to room temperature in air. The conditions for the high-temperature calcination may include: a temperature of 1200-1300°C and a time of 4-6h. In the above process, magnesium oxide can protect the zirconium oxide in the mixture, preventing it from degenerating from a tetragonal form to a monoclinic form during the cooling process, and ensuring that the zirconium oxide in the final mixture is a tetragonal form.
[0144] According to some embodiments of the present invention, preferably, in step (C2), the particle size of the dispersant is 100-400 mesh, preferably 120-180 mesh.
[0145] According to some embodiments of the present invention, preferably, in step (C2), the mass ratio of the nickel precursor to the dispersant calculated as nickel element is (1-10):1, preferably (1.5-5.67):1.
[0146] According to some embodiments of the present invention, preferably, in step (C2), the mixing can be carried out under stirring conditions. The stirring conditions and methods can be conventionally selected in the art and are not particularly limited. For example, non-ferromagnetic equipment can be used for stirring. Preferably, the mixing conditions include: temperature of 20-50°C, time of 20-60min, and rotation speed of 200-400rpm.
[0147] According to some embodiments of the present invention, in step (C3), water is used to adjust the pH value of the lower layer liquid in the layered liquid to 7-9, and then the water in the lower layer liquid is removed, so that the protective agent wraps the catalyst particles.
[0148] According to some embodiments of the present invention, preferably, in step (C3), water is used to adjust the pH value of the lower layer liquid to 7.5-8.
[0149] According to some embodiments of the present invention, preferably, in step (C3), the pH value is adjusted by adding water to the lower layer of the layered liquid for multiple washings until the pH value of the lower layer satisfies the above range. The washing can be performed using a washing liquid conventionally used in the art, such as deionized water.
[0150] Preferably, the washing can be performed by adding water to the lower layer of the layered liquid and then removing the water. The method of removing the water includes: performing solid-liquid separation on the layered liquid to remove the water in the lower layer of the layered liquid. There is no particular limitation on the method of solid-liquid separation, which can be a conventional choice in the art, for example, at least one of filtration, centrifugal separation and gravity sedimentation. It should be noted here that the liquid separated by the solid-liquid separation operation is the water in the lower layer of the layered liquid, excluding the protective agent in the upper layer, and the remaining product includes the protective agent and catalyst particles.
[0151] More preferably, the method of removing water includes: slowly filtering the layered liquid, filtering out the water in the lower layer liquid from below, and stopping when the interface of the upper layer liquid is tangent to the filter outlet, so that the protective agent wraps the catalyst particles. The catalyst particles have a certain fluidity when wrapped by the protective agent, and are particularly suitable for slurry bed reactors.
[0152] According to some embodiments of the present invention, in order to prevent the obtained low-temperature methanation catalyst from being oxidized, preferably, the low-temperature methanation catalyst is stored in a sealed container, for example, the container may be sealed and filled with nitrogen.
[0153] According to some embodiments of the present invention, preferably, in step (1), the particle size of the low-temperature methanation catalyst is 120-180 mesh.
[0154] According to some embodiments of the present invention, preferably, in step (1), the inert heat-conducting medium in the slurry bed reactor is liquid paraffin and / or solid paraffin; preferably, the boiling point of the liquid paraffin is higher than 300°C; the melting point of the solid paraffin is lower than 260°C and the boiling point is higher than 300°C.
[0155] According to some embodiments of the present invention, preferably, in step (1), the volume ratio of the catalyst I to the inert heat-conducting medium is 1:15-25.
[0156] According to some embodiments of the present invention, preferably, in step (1), the conditions of the methanation reaction include: a temperature of 260-340°C, a pressure of 1-4 MPa, and a volume space velocity of 1500-2000 h -1 , stirring speed is 1000-1500rpm.
[0157] According to some embodiments of the present invention, preferably, in step (1), the content of paraffin vapor in the outlet process gas containing paraffin is not higher than 2000 ppm, preferably not higher than 1000 ppm, more preferably 50-1000 ppm.
[0158] According to some embodiments of the present invention, preferably, the water-wax molar ratio in the outlet process gas containing paraffin is higher than 10.
[0159] According to some embodiments of the present invention, preferably, the outlet process gas containing paraffin has a CO content of 3-5% by volume, a CO2 content of 7-10% by volume, a H2 content of 37-55% by volume, a CH4 content of 15-26.5% by volume, and a water vapor content of 15-26.5% by volume.
[0160] According to some embodiments of the present invention, preferably, the pressure of the outlet process gas containing paraffin is 2.0-4.0 MPa, preferably 2.5-3.5 MPa; the temperature is 260-350°C, preferably 270-320°C.
[0161] According to some embodiments of the present invention, in step (2), the outlet process gas is contacted with the catalyst II for an adiabatic methanation reaction. Under the high-temperature methanation catalytic effect and high-temperature dewaxing catalytic effect of the catalyst II, the upstream slurry bed synthesis gas methanation process gas with paraffin as slurry can directly undergo an adiabatic methanation reaction without cooling or separation. In the above process, the methanation reaction and the paraffin cracking reaction occur simultaneously, and a high-temperature outlet process gas free of paraffin can be obtained.
[0162] According to some embodiments of the present invention, preferably, in step (2), the volume ratio of the paraffin cracking catalyst to the high temperature methanation catalyst is 0.5-1:1.
[0163] According to some embodiments of the present invention, in step (2), the high temperature methanation catalyst can be a high temperature methanation catalyst with methanation catalytic effect conventionally used in the art (usage temperature is usually 500-700°C), and there is no particular limitation on this, which can achieve the purpose of the present invention to a certain extent. Preferably, the high temperature methanation catalyst includes a carrier and an active component and an auxiliary agent supported on the carrier, wherein the active component is nickel and / or nickel oxide; the carrier is at least one of aluminum oxide, magnesium oxide, magnesium aluminum spinel, zirconium oxide, calcium oxide and silicon dioxide, preferably magnesium aluminum spinel; the auxiliary agent is La2O3 and / or CeO2.
[0164] According to a preferred embodiment of the present invention, the high temperature methanation catalyst is a high temperature methanation catalyst whose carrier is magnesium aluminum spinel and which supports Ni and La2O3.
[0165] According to some embodiments of the present invention, preferably, in step (2), based on the total amount of the high-temperature methanation catalyst, the content of the active component calculated as nickel is 5-20wt%, the content of the auxiliary agent is 0.1-5wt%, and the content of the carrier is 75-94.9wt%.
[0166] According to some embodiments of the present invention, preferably, in step (2), the particle size of the high temperature methanation catalyst is 20-40 mesh.
[0167] According to some embodiments of the present invention, preferably, in step (2), the conditions of the adiabatic methanation reaction include: pressure of 2.0-4.0 MPa, preferably 2.5-3.5 MPa; inlet temperature of 260-350°C, preferably 270-320°C; hot spot temperature of 500-700°C, preferably 550-650°C; volume space velocity of 1000-10000h -1 , preferably 2000-5000h -1 .
[0168] A second aspect of the present invention provides a system for producing natural gas by methanation of synthesis gas, the system comprising a methanation unit and a refining unit connected in series, wherein the methanation unit comprises at least one slurry bed reactor, the refining unit comprises at least one adiabatic fixed bed reactor, and the outlet of the slurry bed reactor is connected to the inlet of the adiabatic fixed bed reactor.
[0169] According to some embodiments of the present invention, preferably, the outlet of the slurry bed reactor is connected to the inlet of the adiabatic fixed bed reactor through a pipeline.
[0170] Preferably, valves and one-way check valves are sequentially arranged on the pipeline along the flow direction of the logistics.
[0171] The method and system for producing natural gas by methanation of synthesis gas provided by the present invention are further described in detail below in conjunction with the accompanying drawings.
[0172] The present invention illustratively provides a system for producing natural gas by methanation of syngas according to an embodiment, Figure 1 The system comprises a methanation unit and a refining unit connected in series, wherein the methanation unit comprises a slurry bed reactor 1, the refining unit comprises an adiabatic fixed bed reactor 4, and the outlet of the slurry bed reactor 1 is connected to the inlet of the adiabatic fixed bed reactor 4 through a pipeline; along the direction of the flow of the logistics, the pipeline is also provided with a valve 2 and a one-way check valve 3 in sequence.
[0173] The present invention will be described in detail below through examples.
[0174] In the following examples and comparative examples, unless otherwise specified, the raw materials used are all commercially available.
[0175] Light magnesium oxide was purchased from Nanjing Pharmaceutical Company, the model / brand was industrial grade, purity>99wt%, and average particle size was 0.063mm;
[0176] Pseudo-boehmite was purchased from Shandong Aluminum Company, model / brand LSi-pfd-7, with an Al2O3 content of 70wt% and an average particle size of 0.09mm;
[0177] Nickel nitrate was purchased from Nanjing Chemical Reagent Factory, model / brand AR, purity>99wt%;
[0178] The high-temperature methanation catalyst was purchased from Sinopec Nanjing Chemical Research Institute Co., Ltd., and the model / brand is NCJ-1; its composition is: Ni: 15 mass%, La2O3: 0.5 mass%, and the rest is magnesium aluminum spinel; the original particle size of the catalyst is cylindrical particles of φ5*5mm, which are ground using a planetary grinder to a particle size of 20-40 mesh.
[0179] In the following examples and comparative examples, unless otherwise specified, the test equipment used are all commercially available products.
[0180] The XRD spectrum of the carrier was measured by X-ray diffractometer, and the powder X-ray diffractometer was purchased from Bruker, model D8 advance;
[0181] The grain size was obtained by X-ray diffractometer test;
[0182] The pore volume and average pore diameter were obtained by BET adsorption test;
[0183] The content of hydrocarbons was obtained by chromatography, and the content of hydrocarbons was analyzed by Agilent 8890 three-valve five-column FID.
[0184] The following preparation examples are used to illustrate the paraffin cracking catalyst and its preparation method provided by the present invention.
[0185] Preparation Example A1
[0186] (S1) Light magnesium oxide (400 g), pseudo-boehmite (1450 g), a pore-enlarging agent, a binder and a solvent are contacted and mixed and ground, sieved, dried, formed and first calcined in sequence to obtain a carrier, and its XRD test results are as follows: Figure 2 As shown in the figure, it can be seen that it has obvious magnesia-alumina spinel characteristic peaks at 2θ=37.2°, 45.4° and 66.25°, indicating that the main body of the carrier is magnesia-alumina spinel (MgAl2O4), and there is a main peak of magnesium oxide characteristic at 2θ=42.9°, the main peak is sharp and has low intensity, and there is no main peak of aluminum oxide characteristic at 2θ=67.2°. Its composition and property parameters are shown in Table 1; Among them:
[0187] The conditions for the first calcination are: temperature 900°C; time 6h;
[0188] The pore-enlarging agent is nitric acid, and the dosage ratio of nitric acid to magnesium oxide is 1 mL: 50 g;
[0189] The binder is sodium carboxymethyl cellulose, and the mass ratio of sodium carboxymethyl cellulose to magnesium oxide is 1:21.6;
[0190] The solvent is deionized water, and the volume ratio of deionized water to the pore-enlarging agent is 100:1;
[0191] The sieve used for sieving is 10 mesh; the drying conditions are: temperature 120℃; time 6h;
[0192] The size of the catalyst particles obtained by molding is Φ5*5mm;
[0193] (S2) contacting the above-mentioned carrier (94g) with the active component precursor for a first impregnation, then filtering the obtained product, and then drying and second calcining the obtained solid in sequence I to obtain an intermediate; wherein:
[0194] The active component precursor is manganese nitrate, which is provided in the form of a 50 wt % manganese nitrate aqueous solution;
[0195] The conditions for the first immersion were: temperature 70°C; time 2h;
[0196] The drying conditions are: temperature 120°C; time 6h;
[0197] The conditions of the second calcination I are: temperature 420°C; time 4h;
[0198] (S3) contacting the intermediate with the auxiliary agent precursor for a second impregnation, filtering the obtained product, and then drying and second calcining the obtained solid in sequence II; wherein:
[0199] The additive precursor is lanthanum nitrate, which is provided in the form of a 4 wt % lanthanum nitrate aqueous solution;
[0200] The conditions for the second immersion are: temperature 70°C; time 2h;
[0201] The drying conditions are: temperature 120°C; time 6h;
[0202] The conditions of the second calcination II are: temperature 420°C; time 4h;
[0203] A paraffin cracking catalyst was obtained, wherein, based on the total amount of the paraffin cracking catalyst, the content of manganese dioxide was 5% by mass, the content of lanthanum oxide was 1% by mass, and the rest was a carrier.
[0204] The following preparation examples are used to illustrate the bifunctional catalyst provided by the present invention and its preparation method
[0205] Preparation Example B1
[0206] (S1) Light magnesium oxide (400 g), pseudo-boehmite (1450 g), a pore-enlarging agent, a binder and a solvent are contacted and mixed and ground, sieved, dried, formed and first calcined in sequence to obtain a carrier, and its XRD test results are as follows: Figure 2 As shown in the figure, it can be seen that it has obvious magnesia-alumina spinel characteristic peaks at 2θ=37.2°, 45.4° and 66.25°, indicating that the main body of the carrier is magnesia-alumina spinel (MgAl2O4), and there is a main peak of magnesium oxide characteristic at 2θ=42.9°, the main peak is sharp and has low intensity, and there is no main peak of aluminum oxide characteristic at 2θ=67.2°. Its composition and property parameters are shown in Table 1; Among them:
[0207] The conditions for the first calcination are: temperature 900°C; time 6h;
[0208] The pore-enlarging agent is nitric acid, and the dosage ratio of nitric acid to magnesium oxide is 1 mL: 50 g;
[0209] The binder is sodium carboxymethyl cellulose, and the mass ratio of sodium carboxymethyl cellulose to magnesium oxide is 1:21.6;
[0210] The solvent is deionized water, and the volume ratio of deionized water to the pore-enlarging agent is 100:1;
[0211] The sieve used for sieving is 10 mesh; the drying conditions are: temperature 120℃; time 6h;
[0212] The size of the catalyst particles obtained by molding is Φ5*5mm;
[0213] (S2) contacting the above-mentioned carrier (149 g) with the active component precursor I for a first impregnation, then filtering the obtained product, and then drying and second calcining the obtained solid in sequence I to obtain an intermediate I; wherein:
[0214] The active component precursor I is nickel nitrate, which is provided in the form of a 60 wt % nickel nitrate aqueous solution;
[0215] The conditions for the first immersion were: temperature 70°C; time 2h;
[0216] The drying conditions are: temperature 120°C; time 6h;
[0217] The conditions of the second calcination I are: temperature 420°C; time 4h;
[0218] (S3) contacting the intermediate I with the active component precursor II for a second impregnation, filtering the obtained product, and then drying and second calcining the obtained solid in sequence II to obtain the intermediate II; wherein:
[0219] The active component precursor II is manganese nitrate, which is provided in the form of a 50 wt % manganese nitrate aqueous solution;
[0220] The conditions for the second immersion are: temperature 70°C; time 2h;
[0221] The drying conditions are: temperature 120°C; time 6h;
[0222] The conditions of the second calcination II are: temperature 420°C; time 4h;
[0223] (S4) contacting the intermediate II with the auxiliary agent precursor for a third impregnation, filtering the obtained product, and then drying and second calcining the obtained solid in sequence III; wherein:
[0224] The additive precursor is lanthanum nitrate, which is provided in the form of a 4 wt % lanthanum nitrate aqueous solution;
[0225] The conditions for the third immersion are: temperature 70°C; time 2h;
[0226] The drying conditions are: temperature 120°C; time 6h;
[0227] The conditions of the second calcination III are: temperature 420°C; time 4h;
[0228] (S5) contacting the product obtained in step (S4) with hydrogen for reduction; wherein:
[0229] The reduction conditions are: temperature 450°C; time 4h;
[0230] A bifunctional catalyst is obtained, wherein, based on the total amount of the bifunctional catalyst, the content of nickel is 15% by mass, the content of manganese dioxide is 10% by mass, the content of lanthanum oxide is 0.5% by mass, and the rest is a carrier.
[0231] Table 1
[0232]
[0233] Note: Mg:Al refers to the molar ratio of Mg to Al in the carrier (calculated by feed amount);
[0234] The average pore size and pore volume are the average pore size and pore volume of MgAl2O4.
[0235] The following preparation examples are used to illustrate the low-temperature methanation catalyst and its preparation method provided by the present invention.
[0236] Preparation Example C1
[0237] (S1) in the presence of water, contacting a nickel precursor with a reducing agent to perform a reduction reaction to obtain a reduction product; wherein:
[0238] The nickel precursor is nickel nitrate, which is provided in the form of a nickel precursor aqueous solution, wherein the nickel precursor aqueous solution is obtained by dissolving 200 g of nickel nitrate pentahydrate (containing 43.5 g of nickel element) in deionized water, and the concentration of nickel element in the nickel precursor aqueous solution is 1.5 mol / L;
[0239] The reducing agent is sodium borohydride, which is provided in the form of a reducing agent aqueous solution, wherein the concentration of sodium borohydride in the reducing agent aqueous solution is 2 mol / L;
[0240] The molar ratio of the reducing agent to the nickel precursor calculated as nickel element is 1.5:1;
[0241] The contacting step is specifically as follows: under oscillation, the nickel precursor aqueous solution is added dropwise to the reducing agent aqueous solution; the oscillation frequency is 20 Hz; the dropping speed is 4 drops / second;
[0242] The conditions for the reduction reaction are: temperature of 20°C ± 2°C, time of 2h; during the reduction reaction, after the addition is completed, the product is allowed to precipitate freely, and a magnetic substance is used below to assist precipitation;
[0243] The XRD pattern of the reduction product is as follows Figure 3 As shown in the figure, it can be seen that the nickel contained in the reduction product is amorphous nickel;
[0244] (S2) in the presence of a protective agent, mixing the reduction product with a dispersant, and allowing the resulting mixture to stand for stratification to form a stratified liquid; wherein:
[0245] The protective agent is liquid paraffin; the layered liquid includes an upper layer liquid and a lower layer liquid, the upper layer liquid contains the above protective agent, and the lower layer liquid contains water and catalyst particles, and the catalyst particles contain amorphous nickel and the above dispersant; the amount of protective agent used is such that the thickness of the upper layer liquid is 2.5 cm;
[0246] The dispersant is a mixture of zirconium oxide and magnesium oxide, wherein the mass ratio of zirconium oxide to magnesium oxide is 6:1; the crystal form of zirconium oxide is tetragonal; the particle size of the dispersant is 120-180 mesh; the preparation process of the dispersant is specifically as follows: sieve zirconium oxide powder and magnesium oxide powder respectively, select particles with a particle size of 120-180 mesh and blend them according to the above mass ratio, and then calcine the obtained mixture at 1300°C for 4h to transform zirconium oxide from monoclinic crystal form to tetragonal crystal form, and cool the calcined product to room temperature in air; the XRD pattern of the dispersant is as follows Figure 4 As shown in the figure, it can be seen that the crystal form of zirconium oxide contained in the dispersant is tetragonal;
[0247] The mass ratio of the nickel precursor to the dispersant, calculated on the basis of nickel element, is 3:1;
[0248] The mixing conditions were as follows: temperature of 20°C, time of 20 min, and rotation speed of 200 rpm.
[0249] (S3) using water to adjust the pH value of the lower layer liquid in the layered liquid to 7.5, and then removing the water in the lower layer liquid so that the protective agent wraps the catalyst particles to obtain a methanation catalyst, which is sealed and filled with nitrogen; wherein:
[0250] The specific adjustment method is: add water to the lower layer liquid of the layered liquid for multiple washings until the pH value of the lower layer liquid is 7.5; the specific method of removing water is: slowly filter the layered liquid, filter out the water in the lower layer liquid from the bottom, and stop when the interface of the upper layer liquid is tangent to the filter outlet, so that the protective agent wraps the catalyst particles.
[0251] The methanation catalyst comprises catalyst particles and a protective agent wrapping the catalyst particles, wherein the catalyst particles contain amorphous nickel and a dispersant; based on the total weight of the catalyst particles, the content of amorphous nickel in the catalyst particles is 75% by weight, and the content of the dispersant is 25% by weight.
[0252] In the methanation catalyst, the content of the protective agent was 3 mL relative to 1 g of the catalyst particles.
[0253] XRD detection shows that the methanation catalyst has a diffraction peak with a peak width greater than 5° at 2θ=45±0.2°, indicating that the nickel in the methanation catalyst is amorphous nickel; and the zirconium oxide contained in the methanation catalyst conforms to the peak shape, position and intensity of the tetragonal phase (tetragonal crystal type) in the zirconium oxide standard card.
[0254] The following examples are used to illustrate the method for producing natural gas by methanation of synthesis gas provided by the present invention, wherein the method Figure 1 The system for producing natural gas by methanation of synthesis gas shown in the figure comprises a methanation unit and a refining unit connected in series in sequence, wherein the methanation unit comprises a slurry bed reactor 1, the refining unit comprises an adiabatic fixed bed reactor 4, and the outlet of the slurry bed reactor 1 is connected to the inlet of the adiabatic fixed bed reactor 4 through a pipeline; along the direction of flow of the logistics, a valve 2 and a one-way check valve 3 are also arranged in sequence on the pipeline.
[0255] Example 1
[0256] (1) In a slurry bed reactor, the synthesis gas is contacted with a catalyst I to carry out a methanation reaction to obtain an export process gas containing paraffin; wherein:
[0257] Catalyst I is a low temperature methanation catalyst;
[0258] The inert heat transfer medium in the slurry bed reactor is liquid paraffin, which has a boiling point of 300°C;
[0259] The volume ratio of catalyst I to inert heat-conducting medium is 1:20;
[0260] The conditions for the methanation reaction are: temperature 320°C, pressure 3 MPa, volume space velocity 1600 h -1 , stirring speed is 1200rpm;
[0261] The pressure of the outlet process gas is 3.5 MPa, the temperature is 270°C, and the volume space velocity relative to the volume of catalyst II is 5000 h -1 ;
[0262] The composition of the outlet process gas is: CO content 5 volume%, CO2 content 10 volume%, H2 content 55 volume%, CH4 content 15 volume%, water vapor comes from the water spontaneously generated by the slurry bed methanation reaction, which is carried out by the air flow and has a content of 15 volume at equilibrium, and paraffin vapor content is 50ppm;
[0263] (2) In an adiabatic fixed bed reactor, the outlet process gas is contacted with catalyst II to carry out an adiabatic methanation reaction; wherein:
[0264] In an adiabatic fixed bed reactor, a mixture of paraffin cracking catalyst and high temperature methanation catalyst with a volume ratio of 0.5:1 was loaded, totaling 15 mL;
[0265] The paraffin cracking catalyst is the paraffin cracking catalyst prepared in Preparation Example A1;
[0266] The conditions for the adiabatic methanation reaction are: pressure 3 MPa; inlet temperature 270 °C; hot spot temperature 700 °C; volume space velocity 5000 h -1 ;
[0267] The volume composition of the obtained export process gas is: CO: 0.6%, CO2: 4.2%, H2: 18.6%, CH4: 39.0%, water vapor: 37.6%, C2 hydrocarbons 520ppm, C3 hydrocarbons 80ppm, C4 hydrocarbons 5ppm, and no hydrocarbons above C5.
[0268] In this embodiment, the outlet process gas of the slurry bed reactor is 75NL / h, of which the amount of paraffin vapor is 3.75Ncm 3 / h, and the process gas at the outlet of the adiabatic reactor was paraffin-free. The catalyst was disassembled after 500h of use, dried at 100℃ for 4h and tested. The results are shown in Table 2.
[0269] Example 2
[0270] The method of Example 1 is different from that of Example 1:
[0271] In step (1), the conditions for the methanation reaction are specifically: temperature of 300°C, pressure of 2.5 MPa, volume space velocity of 2000 h -1 , stirring speed is 1200rpm, and the rest are the same, so that the pressure of the process gas at the outlet of the slurry bed is 2.7MPa, the temperature is 320℃, and the volume space velocity is 5000h -1 ;
[0272] Its volume composition is: CO content 4 volume%, CO2 content 9 volume%, H2 content 48 volume%, CH4 content 19.5 volume%, water vapor comes from the water spontaneously generated by the slurry bed methanation reaction, which is carried out by the air flow and has a content of 19.4 volume% at equilibrium; paraffin vapor content is 1000ppm;
[0273] In step (2), the conditions for the adiabatic methanation reaction are as follows: pressure of 3.2 MPa; inlet temperature of 260°C; hot spot temperature of 650°C; volume space velocity of 5000 h -1 ; The rest are the same;
[0274] The volume composition of the obtained export process gas is: CO: 0.5%, CO2: 4.0%, H2: 18.0%, CH4: 39.7%, water vapor: 37.8%, C2 hydrocarbons 540ppm, C3 hydrocarbons 90ppm, C4 hydrocarbons 10ppm, and no hydrocarbons above C5.
[0275] In this embodiment, the process gas at the outlet of the slurry bed reactor is 75 NL / h, of which the amount of paraffin vapor is 75 Ncm 3 / h, and the process gas at the outlet of the adiabatic reactor was paraffin-free. The catalyst was disassembled after 500h of use, dried at 100℃ for 4h and tested. The results are shown in Table 2.
[0276] Example 3
[0277] The method of Example 1 is different from that of Example 1:
[0278] In step (1), the conditions for the methanation reaction are specifically: temperature of 260°C, pressure of 2.75 MPa, volume space velocity of 1800 h -1 , stirring speed is 1100rpm, and the rest are the same, so that the pressure of the process gas at the outlet of the slurry bed is 3.0MPa, the temperature is 300℃, and the volume space velocity is 2000h -1 ;
[0279] Its volume composition is: CO content 3 volume%, CO2 content 7 volume%, H2 content 37 volume%, CH4 content 26.5 volume%, water vapor comes from the spontaneous generation of water in the slurry bed methanation reaction, which is carried out by the air flow and has a content of 26.5 volume% at equilibrium, and paraffin vapor content 500ppm;
[0280] In step (2), the conditions for the adiabatic methanation reaction are specifically as follows: pressure of 2.8 MPa; inlet temperature of 280°C; hot spot temperature of 500°C; volume space velocity of 2000 h -1 ; The rest are the same;
[0281] The volume composition of the obtained export process gas is: CO: 0.3%, CO2: 3.0%, H2: 12.9%, CH4: 42%, water vapor 41.8%, C2 hydrocarbons 400ppm, C3 hydrocarbons 20ppm, C4 hydrocarbons 1ppm, and no hydrocarbons above C5.
[0282] In this embodiment, the process gas at the outlet of the slurry bed reactor is 30 NL / h, of which the paraffin vapor volume is 15 Ncm 3 / h, and the process gas at the outlet of the adiabatic reactor was paraffin-free. The catalyst was disassembled after 500h of use, dried at 100℃ for 4h and tested. The results are shown in Table 2.
[0283] Example 4
[0284] The method of Example 1 is followed, except that in step (2), the catalyst loaded in the adiabatic fixed bed reactor is the bifunctional catalyst prepared in Preparation Example B1; the rest is the same;
[0285] The volume composition of the obtained export process gas is: CO: 0.7%, CO2: 4.4%, H2: 19.7%, CH4: 38.0%, water vapor: 37.2%, C2 hydrocarbons 560ppm, C3 hydrocarbons 90ppm, C4 hydrocarbons 4ppm, and no hydrocarbons above C5.
[0286] In this embodiment, the process gas at the outlet of the slurry bed reactor is 75 NL / h, of which the paraffin vapor volume is 3.75 Ncm 3 / h, and the process gas at the outlet of the adiabatic reactor was paraffin-free. The catalyst was disassembled after 500h of use, dried at 100℃ for 4h and tested. The results are shown in Table 2.
[0287] Example 5
[0288] The method according to Example 4 is different in that:
[0289] In step (1), the conditions for the methanation reaction are specifically: temperature of 300°C, pressure of 3.2 MPa, volume space velocity of 1600 h -1 , stirring speed is 1000rpm, and the rest are the same, so that the pressure of the process gas at the outlet of the slurry bed is 2.7MPa, the temperature is 320℃, and the volume space velocity is 5000h -1 ;
[0290] Its volume composition is: CO content 4 volume%, CO2 content 9 volume%, H2 content 48 volume%, CH4 content 19.5 volume%, water vapor comes from the water spontaneously generated by the slurry bed methanation reaction, which is carried out by the air flow and has a content of 19.4 volume% at equilibrium; paraffin vapor content is 1000ppm;
[0291] In step (2), the conditions for the adiabatic methanation reaction are as follows: pressure of 3.0 MPa; inlet temperature of 290°C; hot spot temperature of 650°C; volume space velocity of 5000 h -1 ; The rest are the same;
[0292] The volume composition of the obtained export process gas is CO: 0.6%, CO2: 4.1%, H2: 18.2%, CH4: 39.5%, water vapor about 37.6%, C2 hydrocarbons 530ppm, C3 hydrocarbons 85ppm, C4 hydrocarbons 15ppm, and no hydrocarbons above C5.
[0293] In this embodiment, the process gas at the outlet of the slurry bed reactor is 75 NL / h, of which the paraffin vapor volume is 75 Ncm 3 / h, and the process gas at the outlet of the adiabatic reactor was paraffin-free. The catalyst was disassembled after 500h of use, dried at 100℃ for 4h and tested. The results are shown in Table 2.
[0294] Comparative Example 1
[0295] The method of Example 2 is followed, except that in step (2), only 15 mL of high temperature methanation catalyst is loaded into the adiabatic fixed bed reactor, and the rest is the same;
[0296] The volume composition of the initial outlet process gas obtained is: CO: 0.5%, CO2: 4.0%, H2: 18.0%, CH4: 39.7%, water vapor is 37.8%, C2 hydrocarbons are 1200ppm, C3 hydrocarbons are 700ppm, C4 hydrocarbons are 90ppm, hydrocarbons above C5 are generated, and paraffin substances are not detected in the initial stage;
[0297] In this comparative example, the process gas at the outlet of the slurry bed reactor is 75 NL / h, of which the paraffin vapor volume is 75 Ncm 3 / h, paraffin substances in the process gas from the adiabatic reactor outlet were detected at the 350th hour. The catalyst was disassembled after 500 hours of use, dried at 100℃ for 4 hours and tested. The results are shown in Table 2.
[0298] Table 2
[0299]
[0300] Note: Fresh sample* refers to the fresh sample of high temperature methanation catalyst
[0301] From the above results, it can be seen that the method provided by the present invention is used to methanate synthesis gas to produce natural gas, which can not only effectively prevent paraffin vapor from covering the pore structure and active center of the catalyst, but also in the above process, the paraffin is decomposed more thoroughly, and no phenomenon of paraffin blocking the catalyst pores is found. In the adiabatic methanation reaction, when no paraffin cracking catalyst is used, the pores of the high-temperature methanation catalyst in Comparative Example 1 are blocked and covered, and the pore size specific surface area is greatly reduced. After burning the paraffin at 450°C, its pore structure is basically restored to the normal size, which shows that the coverage of the paraffin deactivates the catalyst.
[0302] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for producing natural gas by methanation of synthesis gas, characterized in that: The method comprises: (1) In a slurry bed reactor, the synthesis gas is contacted with a catalyst I for a methanation reaction to obtain an export process gas containing paraffin; the catalyst I is a low-temperature methanation catalyst; (2) contacting the outlet process gas with catalyst II to carry out an adiabatic methanation reaction; Wherein, the catalyst II comprises a paraffin cracking catalyst and a high-temperature methanation catalyst; the paraffin cracking catalyst comprises a carrier and an active component and an auxiliary agent loaded on the carrier, wherein the active component is manganese dioxide, the auxiliary agent is La2O3, the carrier is a magnesium-aluminum composite oxide, the magnesium-aluminum composite oxide comprises MgAl2O4, and based on the total amount of the magnesium-aluminum composite oxide, the content of MgAl2O4 is 93-100wt%; based on the total amount of the paraffin cracking catalyst, the content of the active component is 5-15wt%, the content of the auxiliary agent is 0.1-2wt%, and the content of the carrier is 83-94.9wt%; or, The catalyst II is a bifunctional catalyst, which includes a carrier and an active component I, an active component II and an auxiliary agent loaded on the carrier, wherein the active component I is nickel and / or nickel oxide, the active component II is manganese dioxide, the auxiliary agent is La2O3, the carrier is a magnesium-aluminum composite oxide, and the magnesium-aluminum composite oxide includes MgAl2O4, and the content of MgAl2O4 is 93-100wt% based on the total amount of the magnesium-aluminum composite oxide; based on the total amount of the bifunctional catalyst, the content of the active component I in terms of nickel is 10-20wt%, the content of the active component II is 5-15wt%, the content of the auxiliary agent is 0.1-2wt%, and the content of the carrier is 74-85wt%.
2. The method according to claim 1, wherein: The magnesium-aluminum composite oxide further comprises MgO and / or Al2O3, wherein, based on the total amount of the magnesium-aluminum composite oxide, the content of MgO is 0-5wt%, preferably 0-3wt%; the content of Al2O3 is 0-2wt%, preferably 0-1wt%; Preferably, based on the total amount of the magnesium-aluminum composite oxide, the content of MgAl2O4 is 96-100wt%; Preferably, the grain size of MgAl2O4 is less than 20 nm, preferably 4-15 nm, more preferably 5-10 nm; the pore volume is greater than 0.15 mL / g, preferably 0.25-0.35 mL / g, more preferably 0.27-0.33 mL / g; the average pore diameter is 10-50 nm, preferably 10-30 nm, more preferably 13-20 nm; Preferably, in the magnesium-aluminum composite oxide, the molar ratio of Mg to Al is 1:2-2.
04.
3. The method according to claim 1 or 2, wherein: The paraffin cracking catalyst is prepared by a method comprising the following steps: (A1) subjecting a mixture containing magnesium oxide, pseudo-boehmite and a pore-enlarging agent to a first calcination to obtain a carrier; wherein the temperature of the first calcination is 800-1000° C.; (A2) loading the active component precursor and the auxiliary agent precursor onto the carrier, and then subjecting the obtained product to a second calcination; wherein the temperature of the second calcination is lower than the temperature of the first calcination.
4. The method according to claim 3, wherein: In step (A1), the temperature of the first calcination is 850-950°C; the time of the first calcination is 2-10h, preferably 4-8h; Preferably, the magnesium oxide is light magnesium oxide, and the average particle size of the light magnesium oxide is 0.06-0.09 mm; the average particle size of the pseudo-boehmite is 0.06-0.09 mm; the pore-enlarging agent is selected from at least one of oxalic acid, nitric acid, acetic acid and sulfuric acid; Preferably, the usage ratio of the pore-expanding agent to the magnesium oxide is 1 mL: 40-60 g; Preferably, the mixture further contains a binder; the binder is selected from at least one of sesbania powder, stearate, cellulose and its derivatives; Preferably, the mass ratio of the binder to the magnesium oxide is 1:20-25.
5. The method according to claim 3 or 4, wherein: In step (A2), the active component precursor is selected from at least one of manganese nitrate, manganese sulfate and manganese chloride; the auxiliary agent precursor is selected from at least one of lanthanum nitrate, lanthanum chloride and lanthanum sulfate; Preferably, the loading method is an impregnation method; the impregnation conditions include: a temperature of 60-80°C; a time of 0.5-2h; Preferably, the active component precursor is first loaded on the carrier to obtain an intermediate, and then the auxiliary agent precursor is loaded on the intermediate; Preferably, the conditions for the second calcination include: a temperature of 350-500° C., preferably 400-450° C.; and a time of 4-10 h, preferably 4-8 h.
6. The method according to claim 1 or 2, wherein: The bifunctional catalyst is prepared by a method comprising the following steps: (B1) subjecting a mixture containing magnesium oxide, pseudo-boehmite and a pore-enlarging agent to a first calcination to obtain a carrier; wherein the temperature of the first calcination is 800-1000° C.; (B2) loading the active component precursor I, the active component precursor II and the auxiliary agent precursor on the carrier, and then performing a second calcination on the obtained product; wherein the temperature of the second calcination is lower than the temperature of the first calcination.
7. The method according to claim 6, wherein: In step (B1), the temperature of the first calcination is 850-950°C; the time of the first calcination is 2-10h, preferably 4-8h; Preferably, the magnesium oxide is light magnesium oxide, and the average particle size of the light magnesium oxide is 0.06-0.09 mm; the average particle size of the pseudo-boehmite is 0.06-0.09 mm; the pore-enlarging agent is selected from at least one of oxalic acid, nitric acid, acetic acid and sulfuric acid; Preferably, the usage ratio of the pore-expanding agent to the magnesium oxide is 1 mL: 40-60 g; Preferably, the mixture further contains a binder; the binder is selected from at least one of sesbania powder, stearate, cellulose and its derivatives; Preferably, the mass ratio of the binder to the magnesium oxide is 1:20-25.
8. The method according to claim 6 or 7, wherein: In step (B2), the active component precursor I is selected from at least one of nickel nitrate, nickel chloride and nickel sulfate; The active component precursor II is selected from at least one of manganese nitrate, manganese sulfate and manganese chloride; The auxiliary agent precursor is selected from at least one of lanthanum nitrate, lanthanum chloride and lanthanum sulfate; Preferably, the loading method is an impregnation method; the impregnation conditions include: a temperature of 60-80°C; a time of 0.5-2h; Preferably, the active component precursor I is first loaded on the carrier to obtain an intermediate I, and then the active component precursor II is loaded on the intermediate I to obtain an intermediate II, and finally the auxiliary agent precursor is loaded on the intermediate II; Preferably, the conditions of the second calcination include: a temperature of 350-500°C, preferably 400-450°C; a time of 4-10h, preferably 4-8h; Preferably, the method further comprises: contacting the product obtained by the second calcination in step (B2) with a reducing gas for reduction.
9. The method according to claim 1 or 2, wherein: In step (1), the low-temperature methanation catalyst comprises catalyst particles and a protective agent wrapping the catalyst particles, the catalyst particles contain amorphous nickel and a dispersant; the dispersant is a mixture of zirconium oxide and magnesium oxide, in which the mass ratio of zirconium oxide to magnesium oxide is (1-10):1, preferably (3-6):1; the crystal form of the zirconium oxide is tetragonal; Preferably, in the XRD spectrum of the low-temperature methanation catalyst, there is a diffraction peak with a peak width greater than 5° at 2θ=45±0.2°; Preferably, in the low-temperature methanation catalyst, the content of the protective agent is 2-4 mL relative to 1 g of the catalyst particles; Preferably, based on the total weight of the catalyst particles, the content of amorphous nickel in the catalyst particles is 65-75% by weight, and the content of the dispersant is 25-35% by weight.
10. The method according to claim 9, wherein: The mixture of zirconium oxide and magnesium oxide is prepared by a method comprising the following steps: The mixture obtained by mixing zirconium oxide powder and magnesium oxide powder is subjected to high temperature roasting, wherein the conditions of the high temperature roasting include: a temperature of 1200-1300° C. and a time of 4-6 hours; Preferably, the particle size of the zirconium oxide powder and magnesium oxide powder is 100-400 mesh; Preferably, the particle size of the dispersant is 100-400 mesh; Preferably, the protective agent is liquid paraffin; Preferably, the particle size of the low temperature methanation catalyst is 120-180 mesh.
11. The method according to claim 9 or 10, wherein: The low-temperature methanation catalyst is prepared by a method comprising the following steps: (C1) contacting the nickel precursor with a reducing agent in the presence of water to perform a reduction reaction to obtain a reduction product; (C2) mixing the reduction product with a dispersant in the presence of a protective agent, and allowing the obtained mixture to stand for stratification to form a stratified liquid; wherein the stratified liquid comprises an upper layer liquid and a lower layer liquid, the upper layer liquid contains the protective agent, the lower layer liquid contains water and catalyst particles, and the catalyst particles contain amorphous nickel and a dispersant; (C3) adjusting the pH value of the lower layer liquid in the layered liquid to 7-9 using water, and then removing the water in the lower layer liquid, so that the protective agent wraps the catalyst particles.
12. The method according to claim 11, wherein: In step (C1), the nickel precursor is selected from at least one of nickel nitrate, nickel chloride and nickel acetate; Preferably, the reducing agent is a borohydride, preferably sodium borohydride and / or potassium borohydride; Preferably, the molar ratio of the reducing agent to the nickel precursor calculated as nickel element is (1-2.5):1; Preferably, the reduction reaction conditions include: temperature of 15-25°C, time of 1-3h; Preferably, in step (C2), the mass ratio of the nickel precursor to the dispersant, calculated as nickel element, is (1-10):1; Preferably, the amount of the protective agent is such that the thickness of the upper layer liquid is 2-3 cm; Preferably, the mixing conditions include: temperature of 20-50°C, time of 20-60min, and rotation speed of 200-400rpm; Preferably, in step (C3), water is used to adjust the pH value of the lower layer liquid to 7.5-8.
13. The method according to any one of claims 1 to 12, wherein: In step (1), the inert heat-conducting medium in the slurry bed reactor is liquid paraffin and / or solid paraffin; Preferably, the boiling point of the liquid paraffin is higher than 300°C; the melting point of the solid paraffin is lower than 260°C and the boiling point is higher than 300°C; Preferably, in step (1), the volume ratio of the catalyst I to the inert heat-conducting medium is 1:15-25; Preferably, in step (1), the conditions of the methanation reaction include: temperature of 260-340°C, pressure of 1-4 MPa, volume space velocity of 1500-2000 h -1 , stirring speed is 1000-1500rpm.
14. The method according to any one of claims 1 to 12, wherein: In step (1), the content of paraffin vapor in the outlet process gas containing paraffin is not higher than 2000 ppm, preferably not higher than 1000 ppm, more preferably 50-1000 ppm; Preferably, the water-to-wax molar ratio in the paraffin-containing outlet process gas is higher than 10; Preferably, the content of CO in the outlet process gas containing paraffin is 3-5% by volume, the content of CO2 is 7-10% by volume, the content of H2 is 37-55% by volume, the content of CH4 is 15-26.5% by volume, and the content of water vapor is 15-26.5% by volume; Preferably, the pressure of the outlet process gas containing paraffin is 2.0-4.0 MPa, preferably 2.5-3.5 MPa; the temperature is 260-350°C, preferably 270-320°C.
15. The method according to any one of claims 1 to 12, wherein: In step (2), the volume ratio of the paraffin cracking catalyst to the high temperature methanation catalyst is 0.5-1:1; Preferably, in step (2), the high temperature methanation catalyst comprises a carrier and an active component and an auxiliary agent supported on the carrier, wherein the active component is nickel and / or nickel oxide; the carrier is at least one of aluminum oxide, magnesium oxide, magnesium aluminum spinel, zirconium oxide, calcium oxide and silicon dioxide, preferably magnesium aluminum spinel; the auxiliary agent is La2O3 and / or CeO2; Preferably, based on the total amount of the high-temperature methanation catalyst, the content of the active component in terms of nickel is 5-20wt%, the content of the auxiliary agent is 0.1-5wt%, and the content of the carrier is 75-94.9wt%; Preferably, the particle size of the high temperature methanation catalyst is 20-40 mesh.
16. The method according to any one of claims 1 to 12, wherein: In step (2), the conditions of the adiabatic methanation reaction include: pressure of 2.0-4.0 MPa, preferably 2.5-3.5 MPa; inlet temperature of 260-350°C, preferably 270-320°C; hot spot temperature of 500-700°C, preferably 550-650°C; volume space velocity of 1000-10000h -1 , preferably 2000-5000h -1 .
17. A system for producing natural gas by methanation of synthesis gas, characterized in that: The system comprises a methanation unit and a refining unit connected in series, wherein the methanation unit comprises at least one slurry bed reactor, the refining unit comprises at least one adiabatic fixed bed reactor, and the outlet of the slurry bed reactor is connected to the inlet of the adiabatic fixed bed reactor.
Citation Information
Patent Citations
Process for synthesizing natural gas by methanation of coal synthesis gas
CN101979476A
Preparation method of catalyst for natural gas preparation through complete methanation of synthesis gas
CN106944085A
Preparation method for methanation catalyst taking magnesium-aluminum composite oxide as carrier
CN109465012A
Process for the preparation of a catalyst for the synthesis of methane
US4510264A